Correlating Fine Needle Aspiration Cytology Results of Mammary Malignancy with Corresponding Ultrasound BIRADS Score - Khaleel, Mohson (Asian Pacific Journal of Cancer Care, 2022)
Objective: Breast mass is a major complaint making women attending any breast clinic. About 10% of the lumps are usually malignant. Triple assessment techniques using clinical examination, ultrasound, and cytology are usually sufficient in reaching the final diagnosis, especially in specialized breast centers. The aim of this study was to assess how accurate ultrasound was in the diagnosis of definite breast cancer according to BIRADS (Breast Imaging Reporting and Data System), and correlate these radiological findings with the results of fineneedle aspiration cytology (FNAC). Methods: A retrospective study included 42 patients who presented with a self-detected breast lump and attending the Early Detection of Breast Tumors clinic in the Oncology Teaching Hospital, Medical City Complex, Baghdad during the period from May 2019 to August 2020. Their age ranged from 29 to 92 years. Patients underwent ultrasound examination after clinical examination and the reported BIRADS score was correlated with the corresponding cytology data. Results: the main ultrasound findings are masses that are either irregular in the majority of cases and this represents 55%, poorly demarcated lesions seen in (26%) while 14% of them were well defined. axillary lymphadenopathy with typical malignant features was noted in (50%). FNAC revealed mammary carcinoma in (93%); while severe atypia was seen in 7%, BIRADS V score was assigned in 76%, of breast exam BIRADS IV in 21% while the remaining 3% were in BIRADS III category. By correlating these ultrasound findings of BIRADS with FNAC results, the ultrasound accuracy in the diagnosis of breast cancer was reaching to 90%. Conclusion: Ultrasonography represents an accurate diagnostic radiological modality for any breast lesion and is thus considered a recommended method for assessment of underlying cause responsible for palpable breast mass or any presenting symptoms related to the breasts. Its value was demonstrated in characterizing the mass lesion, assessing its location, its echo texture, margin, and size, it has a major role in analyzing the axilla for normal or pathological lymph nodes.